2015
DOI: 10.1186/2046-4053-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Methods of a multi-faceted rapid knowledge synthesis project to inform the implementation of a new health service model: Collaborative Emergency Centres

Abstract: BackgroundThe aim of this rapid knowledge synthesis was to provide relevant research evidence to inform the implementation of a new health service in Nova Scotia, Canada: Collaborative Emergency Centres (CECs). CECs propose to deliver both primary and urgent care to rural populations where traditional delivery is a challenge. This paper reports on the methods used in a rapid knowledge synthesis project to provide timely evidence to policy makers about this novel healthcare delivery model.MethodsWe used a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The work needed to occur quickly, before onset of policy changes in complex care programs. A choice was made to employ principles of rapid knowledge synthesis and engagement strategies . The public funder provided in‐kind support to mitigate the demand of the rapid time cycle.…”
Section: Methodsmentioning
confidence: 99%
“…The work needed to occur quickly, before onset of policy changes in complex care programs. A choice was made to employ principles of rapid knowledge synthesis and engagement strategies . The public funder provided in‐kind support to mitigate the demand of the rapid time cycle.…”
Section: Methodsmentioning
confidence: 99%
“…None of the included documents conducted a formal evaluation of engagement; measurement tools specific to engagement were not identified. The authors of one paper asked participating knowledge users to answer an anonymous survey and 100% reported that the information provided in the review was “very” or “somewhat” useful in their decision-making [ 58 ]. One study [ 46 ] suggested ways to measure engagement in future research, including tracking how the research question, eligibility criteria, or other aspects of the review were modified after engagement, comparing reviews on the same topic with engagement and without engagement, retrospectively evaluating reviews that were conducted without engagement to determine their impact, or deliberately phasing in engagement at different parts of the process to measure how the engagement impacted the review.…”
Section: Resultsmentioning
confidence: 99%
“…Two conceptual frameworks were identified that provided a structure and mechanism to facilitate knowledge user engagement in knowledge synthesis. These were the 7Ps of Stakeholder Engagement and Six Stages of Research framework [ 58 ] and a conceptual framework on the models and mechanisms for engaging policy-makers in systematic reviews that focus on health policy and systems research [ 47 ]. An additional framework can also be used: the online survey patient and public engagement questionnaire (PPEQ) [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, recently, the Nova Scotia provincial government funded a rapid evidence review on collaborative emergency centres to inform decision-making for this program. 35 EMS stakeholders can use existing EBP processes established within Canada, as well as International EMS systems to advance their local systems. EM and EMS physicians who are in the position of developing and overseeing local practice guidelines need not feel they are alone in their venture.…”
Section: Process: Strengths and Implementation Strategiesmentioning
confidence: 99%